2018
DOI: 10.1016/j.jenvp.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the forest down to save your face: Narcissistic national identification predicts support for anti-conservation policies

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 36 publications
(51 reference statements)
4
68
0
Order By: Relevance
“…A potentially fertile ground for future research would be to examine other consequences of collective narcissism and secure ingroup identification, especially for intra‐group processes. Overall, we expect collective narcissism to predict less concern about the well‐being of other group members and greater concern with maintaining a positive image of the ingroup for the outside world (Cichocka, ; Cichocka & Cislak, ; Cislak, Wojcik & Cichocka, ). While secure ingroup identification might predict concern with how the ingroup is received by others, this should be trumped by being concern about the well‐being of other group members.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially fertile ground for future research would be to examine other consequences of collective narcissism and secure ingroup identification, especially for intra‐group processes. Overall, we expect collective narcissism to predict less concern about the well‐being of other group members and greater concern with maintaining a positive image of the ingroup for the outside world (Cichocka, ; Cichocka & Cislak, ; Cislak, Wojcik & Cichocka, ). While secure ingroup identification might predict concern with how the ingroup is received by others, this should be trumped by being concern about the well‐being of other group members.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses indicated that the rejection of immigrants, perceived as a threat to economic superiority and the British way of life, were behind the association between collective narcissism and the Brexit vote (Golec de Zavala et al, ). In addition, collective narcissism was associated with support for the populist governments and its particular policies in Poland (Cislak, Wojcik, & Cichocka, ; Golec de Zavala, ; Marchlewska et al, ) and in Hungary (Lantos, ).…”
Section: Concepts Pertaining To Attitudes Towards National Ingroupsmentioning
confidence: 99%
“…For example, outgroup prejudice is negatively associated with national identi cation but positively with national narcissism (Golec de Zavala, Cichocka, & Bilewicz, 2013). National narcissism also predicts concern for maintaining a positive image of the nation than for the well-being of fellow citizens (Cichocka, 2016;Cislak et al, 2018;Marchlewska et al, 2020). Thus, national narcissists may be less inclined to engage in behaviours to prevent the spread of COVID-19 (Nowak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%